EFL Teachers’ Readiness in Using Technology to Teach English in A Public Junior High School - Ramadhani, Firyal Alvi; Ariani, Musli; Fitriyah, Siti Masrifatul (EFL Education Journal, 2023)
This study focuses on EFL teachers’ readiness in using technology in teaching English. According to the Technology Acceptance Model (TAM) framework (Davis, 1989), people’s perceived ease of use and perceived usefulness will lead to the person’s attitude toward using technology. Qualitative case study was carried out to explore EFL teachers’ readiness to use technology in teaching. The data from interview analyzed using thematic analysis. To enrich the data, observation also employed. In this case, teachers’ attitude towards using is almost in the same height and generally low. However, their perceived ease of use and perceived usefulness result are varying. Based on the findings in my study, I found that the teachers feel that technology for learning is very useful for them. However, they feel it is not easy to use and also somewhat those teachers were resistant to accept the existence of technology in teaching. These shows that that the teachers in the school are not ready yet to use technology in teaching English.